Metal artefact reduction in low-dose computed tomography: Benefits of tin prefiltration versus postprocessing of dual-energy datasets over conventional CT imaging. Issue 3 (August 2022) - Huflage, H.; Grunz, J.-P.; Hackenbroch, C.; Halt, D.; Luetkens, K.S.; Alfred Schmidt, A.M.; Patzer, T.S.; Ergün, S.; Bley, T.A.; Kunz, A.S.
Abstract: Introduction: The purpose of this study was to determine the potential for metal artefact reduction in low-dose multidetector CT as these pose a frequent challenge in clinical routine. Investigations focused on whether spectral shaping via tin prefiltration, virtual monoenergetic imaging or virtual blend imaging (VBI) offers superior image quality in comparison with conventional CT imaging. Methods: Using a third-generation dual-source CT scanner, two cadaveric specimens with different metal implants (dental, cervical spine, hip, knee) were examined with acquisition protocols matched for radiation dose with regards to tube voltage and current. In order to allow for precise comparison, and due to the relatively short scan lengths, automatic tube current modulation was disabled. Specifically, the following scan protocals were examined: conventional CT protocols (100/120 kVp), tin prefiltration (Sn 100/Sn 150 kVp), VBI and virtual monoenergetic imaging (VME 100/120/150 keV). Mean attenuation and image noise were measured in hyperdense and hypodense artefacts, in artefact-impaired and artefact-free soft tissue. Subjective image quality was rated independently by three radiologists. Results: Objectively, Sn 150 kVp allowed for the best reduction of hyperdense streak artefacts (p < 0.001), while VME 150 keV and Sn 150 kVp protocols facilitated equally good reduction of hypodense artefacts (p = 0.173). Artefact-impaired soft tissue attenuation was lowest in Sn 150 kVp protocols (p ≤ 0.011), whereas all VME showed significantly less image noise compared to conventional or tin-filtered protocols (p ≤ 0.001). Subjective assessment favoured Sn 150 kVp regarding hyperdense streak artefacts and delineation of cortical bone (p ≤ 0.005). The intraclass correlation coefficient was 0.776 (95% confidence interval: 0.712–0.831; p < 0.001) indicating good interrater reliability. Conclusion: In the presence of metal implants in our cadaveric study, tin prefiltration with 150 kVp offers superior artefact reduction for low-dose CT imaging of osseous tissue compared with virtual monoenergetic images of dual-energy datasets. The delineation of cortical boundaries seems to benefit particularly from spectral shaping. Implications for practice: Low-dose CT imaging of osseous tissue in combination with tin prefiltration allows for superior metal artefact reduction when compared to virtual monoenergetic images of dual-energy datasets. Employing this technique ought to be considered in daily routine when metal implants are present within the scan volume as findings suggest it allows for radiation dose reduction and facilitates diagnosis relevant to further treatment.